Rates of emergency room visits and hospitalizations among refugee and resident children in a tertiary hospital in Turkey - BARIŞ, HATİCE EZGİ; BORAN, PERRAN (My University, 2022)
Evaluation of emergency department (ED) presentation by Syrian refugee children might provide important information about their health care needs. For this purpose, we compared ED presentation of refugee and resident children in a tertiary university hospital in Istanbul, Turkey. Electronic medical records of Syrian refugee children≤18 years old presenting to the ED between January 2013 and July 2019 were retrospectively reviewed and compared with resident children. The study population consisted of 7299 refugees and 690,127 resident children admitted to the ED. High-acuity cases were more frequent in Syrian refugees (2.2% vs 1% p<0.001). One-third of Syrian children were under 12 months of age (31% vs 17%, p<0.001). Syrian children were more commonly hospitalized (7.9% vs 3.1% p<0.001). The median age (and interquartile range – IQR) was lower in hospitalized refugee than in resident children [12 (0–83) months vs 41 (8–111) months, p<0.001]. Rate of intensive care unit hospitalization (13% vs 9.4%, p=0.001) and neonatal hospitalization was higher in Syrians compared to resident children (29% vs 12%, p<0.001). The median NICU stay was longer in refugees [6 (IQR 4–17) days vs 3 (IQR 1–9) days, p<0.001]. Conclusion: Refugee children, as compared to resident children, are more likely to present to the ED with high acuity conditions and at a younger age resulting in higher rates of inpatient admissions. Strategies to increase access to preventive health care services for young refugee children should be explored to decrease ED and hospital services and improve health outcomes.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Armed conflict; Child; Emergency; Healthcare; Refugee; DEPARTMENTS; Armed conflict; Child; Emergency; Healthcare; Refugee